Endoscopic bronchial occlusion with silicone spigots under virtual bronchoscopic navigation. Issue 4 (5th May 2016) - Hayama, Manabu; Sato, Shingo; Shiroyama, Takayuki; Nishida, Takuji; Nishihara, Takashi; Okamoto, Norio
Abstract: A 68‐year‐old woman with interstitial lung disease related to dermatomyositis and systemic scleroderma was admitted to our hospital with fever and dyspnoea. Although the fever was reduced after antibiotic therapy, a left pneumothorax suddenly occurred on day 27 after admission. A continuous air leak persisted despite chest drainage with three tubes and repeated pleurodesis. Chest computed tomography (CT) images showed a cavitary lesion with a pinhole in the left upper division, which was suspected to be the affected lesion with the air leak. Virtual bronchoscopic navigation images were constructed from CT data. Bronchial occlusion with Endobronchial Watanabe Spigots (EWSs) was performed on day 52. Two medium‐sized EWSs were inserted into the left B1 + 2a and B1 + 2b, and the air leak stopped immediately. No procedure‐related adverse events occurred. All three chest tubes were successfully removed by day 60. This case demonstrates that virtual bronchoscopic navigation can improve bronchial occlusion procedures using EWSs. Abstract : A 68‐year‐old female had a left pneumothorax with a persistent air leak despite chest drainage and repeated pleurodesis. Virtual bronchoscopic navigation (VBN) images were constructed from chest computed tomography data. Bronchial occlusion with Endobronchial Watanabe Spigots (EWSs) was performed based on the VBN images, and the air leak stopped immediately.